2018
DOI: 10.1103/physrevb.98.075145
|View full text |Cite
|
Sign up to set email alerts
|

Part-per-million quantization and current-induced breakdown of the quantum anomalous Hall effect

Abstract: In the quantum anomalous Hall effect, quantized Hall resistance and vanishing longitudinal resistivity are predicted to result from the presence of dissipationless, chiral edge states and an insulating two-dimensional bulk, without requiring an external magnetic field. Here, we explore the potential of this effect in magnetic topological insulator thin films for metrological applications. Using a cryogenic current comparator system, we measure quantization of the Hall resistance to within one part per million … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 68 publications
(121 reference statements)
4
71
0
Order By: Relevance
“…As described in fig.35a from ref. [299], the gapless chiral edge state is hosted in the exchange-induced gap in the Dirac spectrum of the topological surface states inside the 3D bulk gap. The Hall 57 resistance is quantized for a Fermi level in the surface-state gap.…”
Section: Further Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in fig.35a from ref. [299], the gapless chiral edge state is hosted in the exchange-induced gap in the Dirac spectrum of the topological surface states inside the 3D bulk gap. The Hall 57 resistance is quantized for a Fermi level in the surface-state gap.…”
Section: Further Perspectivesmentioning
confidence: 99%
“…Accurate comparisons of the Hall resistances measured both in a FTI at zero magnetic field and in a GaAs-based reference standard were recently performed using a CCC-based resistance bridge. Actually, Fox and co-authors [299] have demonstrated the quantization of the Hall resistance with a relative uncertainty of about one part in 10 6 at a temperature of 21 mK for a measurement current of 100 nA in a top-gated 100 µm wide Hall bar made of 6-quintuple-layer sample of Cr 0.12 (Bi 0.26 Sb 0.62 ) 2 Te 3 grown on a GaAs substrate by molecular beam epitaxy (MBE). Limitations in temperature and current are explained by an effective energy gap much lower than expected and strong electron heating in bulk current flow respectively.…”
Section: Further Perspectivesmentioning
confidence: 99%
“…[3][4][5] Dissipationless, chiral 1D conduction is also expected along magnetic domain walls, [6][7][8][9] but explicit experimental confirmation of this prediction has proven elusive.…”
Section: Introductionmentioning
confidence: 99%
“…21 Each jump likely represents rearrangement of the magnetic domain structure. Since within a domain the 2D bulk of an MTI is highly insulating at the lowest temperatures, 3,4 these jumps suggest that domain walls host conductive modes. The set of discrete R yx values is not reproducible between separate magnetic field sweeps, suggesting that the network of magnetic domain walls is complex.…”
Section: Introductionmentioning
confidence: 99%
“…The anomalous Hall effect (AHE), despite being first reported over a hundred years ago, [1] remains of significant modern research interest as its investigation in novel magnetic materials continues to yield rich physics. Recent examples of this are the quantum anomalous Hall effect [2][3][4][5][6][7][8][9][10][11][12], which offers both potential for metrological applications [13,14] and for the academic study of axion electrodynamics [5,12,15,16], as well as reports on alleged contribution to the Hall effect [17][18][19][20][21][22][23][24] associated with skyrmion magnetic textures.…”
mentioning
confidence: 99%